Glyphosate-based Herbicide Exposure Causes Reduction in Endocrine Pancreatic Mass of Female Mice Submitted to Ovarian Hormone Deprivation - Daniel Cesar da Silva; João Lucas de Paula Xavier; Paulo Roberto Ribeiro; Maria Lúcia Bonfleur; Rosane Aparecida Ribeiro (Brazilian Archives of Biology and Technology)
Abstract Glyphosate-based herbicides (GBHs) have been related to various organic impairments, however, its effects on endocrine pancreas and body glucose control are yet unclear. Here, we investigated the effects of GBH exposure on glucose homeostasis and endocrine pancreatic morphology in adult female mice. Furthermore, it was evaluated whether the effects of the herbicide are influenced by circulating concentration of ovarian hormones, particularly estrogen. Adult female C57Bl/6 mice underwent either SHAM operation or bilateral ovariectomy to induce ovarian hormone deprivation. Subsequently, SHAM and ovariectomized (OVX) females received a daily oral gavage of 0.2 mL distilled water (SHAM0 and OVX0 groups), containing or not 0.5 mg/kg (SHAM0.5 and OVX0.5 groups), or 50 mg/kg of GBH (SHAM50 and OVX50 groups) for 60 days. The selection of these doses was based on the regulatory concentrations established for Acceptable Daily Intake (ADI) and No Observable Adverse Effect Level (NOAEL) of glyphosate, respectively. GBH exposure, at both concentrations, did not change body weight, pancreas weight, glucose tolerance or insulin sensitivity in SHAM and OVX mice. However, in OVX females exposed to 50 mg/kg/day, GBH reduced non-β cell area, as well as the islet, β-cell, and non-β cell masses in the pancreas. In SHAM females, a lower dose (0.5 mg/kg/day) of GBH reduced islet and β-cell areas/islet, without altering total endocrine pancreatic mass. These findings suggest that GBH exposure, even at regulatory threshold levels for ADI and NOAEL, may impair pancreatic islet structure. Importantly, the herbicide’s detrimental effects appear to be more pronounced under conditions of low estrogen, such as in OVX females.